Effect of an acid diet allied to sonic toothbrushing on root dentin permeability: An in vitro study - Pinto, Shelon Cristina Souza [UNESP] (2010)
This study quantified alterations in root dentin permeability after exposure to different acid beverages. Twenty-five third molars were sectioned below the cementoenamel junction, the root segment was collected, and the pulp tissue was removed. The root segments were connected to a hydraulic pressure apparatus to measure the permeability of root dentin after the following sequential steps, with 5 specimens in each: 1) phosphoric acid etching for 30 s (maximum permeability), 2) root planning to create new smear layer, 3) exposure to different acid substances for 5 min (orange, cola drink, vinegar, white wine, lemon juice), 4) toothbrushing with sonic toothbrush for 3 min, 5) toothbrushing with sonic toothbrush plus dentifrice for 3 min. Considering step I as 100%, the data were converted into percentage and each specimen was its own control. Data were analyzed statistically by Kruskal-Wallis and Dunn's post test at 5% significance level. All acidic substances increased dentin permeability significantly after scraping (p<0.05). Toothbrushing after exposure to acid substances decreased dentin permeability and the association with dentifrice accentuated the decrease (p<0.05), except for the specimens treated with cola drink. Thus, it may be concluded that all tested acid fruit juices increased dentin permeability, and toothbrushing with or without dentifrice can decrease root dentin permeability after dentin exposure to acid diet.